IMPLEMENTASI KOMUNIKASI PEMBANGUNAN PADA KEGIATAN DAKWAH - Rahima Zakia (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The essence of national development is to build Indonesian people as a whole and the development of the entire Indonesian community. National development in various aspects of animal life is only the responsibility of the government, but demands the participation of various layers of society based on profession and expertise. Whole human development is carried out synergically both physically and mentally. The development of religious aspects as an integral part of national development is the practice of the precepts of the One Godhead. Thus, religion becomes a moral foundation and ethics in society, nation and state. Understanding and practicing religion correctly are expected to support the realization of Indonesian people who are religious, democratic, independent, physically and spiritually qualified, and fulfilled material-spiritual needs. Development basically involves at least three components, namely development communicators, government or community officials, development messages that contain ideas or development programs, and development communicants, namely the wider community, both at the urban and rural levels. In the missionary activities the da'wah interpreter acts as a development communicator to convey development messages, dynamists, motivators, facilitators through oral preaching, writing, and deeds.